PERSEPSI GURU TENTANG PENDIDIKAN KARAKTER (STUDI DI SD PLUS IGM PALEMBANG) - Syaflin, Sylvia Lara (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This research aims to determine: (1) teachers' perceptions about character education and (2) material given by teachers in character education. This research is descriptive research using qualitative approach. Informants in this study are teachers (educators) as many as 6 people consisting of all teachers grade 1 to grade 6. Techniques of determining informants using purposive sampling techniques. Data collection was done by observation, interview, and documentation. The data obtained then processed by descriptive qualitative. The results of this study indicate that: (1) teachers' perceptions of character education show a positive thing, which integrates character education materials into their learning and learning materials, character education is regarded as an essential value in shaping and fortifying the learner's personality; (2) Character education materials (concepts) prepared and taught by teachers (educators) tailored to the substance of the content of certain subject matter, based on the curriculum 2013.